1991
DOI: 10.2166/wst.1991.0570
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Lipid Inhibition in Anaerobic Processes by Introducing a Two-Phase System

Abstract: The inhibitory effect of lipids and prevention of this inhibition in a two-phase anaerobic process were examined using laboratory-scale reactors and batch experiments. Lipids were satisfactorily degraded in a two-phase anaerobic filter while in a single-phase system, inhibition resulted in poor lipid degradation. Unsaturated long-chain fatty acids (LFAs) had a greater inhibitory effect than saturated LFAs. Methane production as well as beta-oxidation (degradation of saturated LFAs) were inhibited by unsaturate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(57 citation statements)
references
References 0 publications
3
51
0
3
Order By: Relevance
“…The maximum lipids removal efficiency, 23.9±2.5%, was found at Period 4, while the maximum double-bond saturation, 25.2±2.9%, was found at Period 2. The maximum values were comparable to the reported values for synthetic wastewater (Komatsu et al, 1991;Kim et al, 2004a). At Period 6 and 7, both parameters decreased considerably.…”
Section: Role and Its Limitation Of The Acidogenic Cstrsupporting
confidence: 87%
See 2 more Smart Citations
“…The maximum lipids removal efficiency, 23.9±2.5%, was found at Period 4, while the maximum double-bond saturation, 25.2±2.9%, was found at Period 2. The maximum values were comparable to the reported values for synthetic wastewater (Komatsu et al, 1991;Kim et al, 2004a). At Period 6 and 7, both parameters decreased considerably.…”
Section: Role and Its Limitation Of The Acidogenic Cstrsupporting
confidence: 87%
“…A pH range of 4.0-6.5 has been reported as optimal for acidogenesis in a general two-phase system (Fox and Pohland, 1994). But, Komatsu et al (1991) reported that a low pH (6.0) hindered acidogenesis because the acidic pH changed LCFAs to an insoluble non-ionized form. It seemed that the pH values did not cause significant adverse effects on reactor performance in the whole Periods, although optimum pH for acidogenesis of lipids-containing wastewaters is still controversial.…”
Section: Role and Its Limitation Of The Acidogenic Cstrmentioning
confidence: 99%
See 1 more Smart Citation
“…The sewage sludge consisted of excess and primary sludge from a wastewater management plant applying EBPR (enhanced biological phosphorus removal). Rapeseed oil was chosen as a co-substrate due to its high LCFA contents, such as oleic acid (52-67 %), linoleic acid (16-25 %) and linolenic acid (6-15 %), and because LCFAs are frequently found in actual wastewaters (Komatsu et al 1991). The OLR depended on the state of each experiment.…”
Section: Laboratory-scale Biogas Digestersmentioning
confidence: 99%
“…This inhibition is due to the presence of long chain fatty acids formed during the hydrolysis of lipids, which causes retardation in methane production (Hanaki et al, 1981). Long chain fatty acids were reported to be inhibitory to methanogenic bacteria (Koster, 1987) but lipids do not cause serious problems in aerobic processes (Komatsu et al, 1991).…”
Section: Anaerobic Treatmentmentioning
confidence: 99%